Фінансовий інжиніринг формування ресурсів як складової антикризового управління сільськогосподарських підприємств - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Клименко, Станіслав; Klymenko, Stanislav; Дербеда, А.І.; Derbeda, Anastasia (Міжнародний університет фінансів спільно з факультетом менеджменту та маркетингу Національного технічного університету України «КПІ», 2023)
В статті висвітлено окремі особливості фінансового інжинірингу при формуванні ресурсів як основної складової антикризового управління сільськогосподарських підприємств. Авторами систематизовано визначення економічного терміну «фінансовий інжиніринг» в розрізі окремих пропозицій наданих різними авторами. Розглянуто переваги інструментів фінансового інжинірингу та сфера їх застосування в системі антикризового управління підприємств аграрного сектору економіки. Зазначено учасники інжинірингового бізнесу з врахуванням зарубіжного досвіду реалізації інжинірингових проектів. Також визначено складові моделі фінансового інжинірингу при формуванні фінансових ресурсів на підприємстві як сукупності створення ефективної системи спрямованої на новітні технології щодо планування, організації і контролю фінансових ресурсів підприємства, що позитивно впливає на фінансові результати сільськогосподарських підприємств. The article highlight some features of financial engineering in the formation of resources as the main component of anti-crisis management of agricultural enterprises. The authors systematized the definition of the economic term "financial engineering" in terms of separate proposals provided by various scientists. The advantages of financial engineering tools and the scope of their application in the anti-crisis management system of enterprises in the agrarian sector of the economy are considered. The participants of the engineering business are specified, taking into account the foreign experience in the implementation of engineering projects. The components of financial engineering models in the formation of financial resources at the enterprise are also determined as a set of creation of an effective system aimed at the latest technologies for planning, organization and control of the financial resources of the enterprise, which positively affects the financial results of agricultural enterprises. The role of participants and financial intermediaries of stock market operations, as well as the areas and directions of their activities: underwriting, securities management, asset management, mortgage coverage management, custody of assets of institutes and pension funds is determined. The types of financial instruments preferred by enterprises when forming a portfolio of financial resources are separated. It has been proven that the financial instruments of the stock market are those that can predict the receipt of income and exist in the form of contracts, securities, options, derivatives, swaps. A mechanism for managing financial risks while ensuring anti-crisis activity of agricultural enterprises is proposed. At the same time, the agricultural enterprise must constantly model the possible consequences of its economic development under conditions of uncertainty and conflict, as well as take into account the factors affecting the level of risk, evaluate them, identify possible losses associated with them. For this purpose, it is necessary to develop the most acceptable ways of overcoming financial risks: risk avoidance; risk acceptance; transfer of risk; risk insurance; pooling of risks, diversification, risk hedging.
Financial engineering of resource formation as a component of anti-crisis management of agricultural enterprises
Keywords: фінансовий інжиніринг; financial engineering; фінансові ресурси; financial resources; фінансовий механізм; financial mechanism; антикризове управління; anticrisis management